Prevenção de fragilidade na pessoa idosa: construção de vídeo educativo - Oliveira, Erika Correia Fonseca de (2022)
Introduction: In the aging process, there is a decline in the vital functions of the body, which leads to the emergence of diseases and reflects in chronic conditions, vulnerability, and consequently, frailty. Considered a geriatric clinical syndrome, frailty can be defined as a state of physiological vulnerability related to age, resulting from decreased homeostatic reserve and reduced ability to cope with negative health outcomes. Objective: The aim of this study was to develop and validate an educational video on physical exercise for the prevention of frailty in older adults. Method: This was a methodological study that developed an educational video on physical exercise for the prevention of frailty in older adults. The study was conducted in three stages: 1) elaboration of an integrative literature review on physical exercises related to frailty prevention in older adults; 2) construction of the video based on evidence and the professional experience of the researcher; 3) validation of the video by expert judges with expertise in the content and method. Results: Based on the scientific evidence from the literature review, the first version of the video was created, containing illustrative scenes organized with a script accompanied by a Likert scale composed of four items, to which degrees of relevance were assigned. After validation by the judges, the second version of the video was developed, which included scenes related to physical exercises for the prevention of frailty in older adults, and these scenes were considered 100% relevant by the judges. Discussion: Physical exercises for older adults are often seen in many studies as a tool for promoting health, associated with benefits such as increased muscle mass and strength, development of balance, strengthening of muscle groups important for stabilization, improvement in gait, and prevention and management of endocrine-metabolic, cardiovascular, respiratory, and neuromuscular diseases. The exercises are considered preventive and/or therapeutic measures for frailty in older adults. Conclusion: The developed video provides information on the importance of engaging in physical exercises for the prevention of frailty in older adults, serving as an educational, interactive, and technologically advanced resource with accessible language that can support older adults in safely and didactically practicing physical exercises, thereby improving their quality of life. It represents a tool for promoting the health of older adults that can be utilized by multidisciplinary teams.